Maligni tumorji mehurja - Sedmak, Boris (Zdravniški vestnik, 2003)
Background. The incidence of bladder cancer is rising in Slovenia and in most countries in the world. Increasing incidence is probably due to aging population and risk factors. Approximately 75-85% of patients present with disease confined to mucosa (Ta-Tis), or submucosa (TI)stage. The other 15-25% have muscle invasion or nodal disease (stages T2-T4, N+) at presentation. Conclusions. The diagnosis of bladder cancer ultimately depends on cystoscopicexamination of the bladder and histopathological evaluation of resected lesion. After transuretral resection (TUR) treatment of superficial bladder tumors (TaT1) will be directed towards the prevention of recurrence and progression with bladder instillation of vaccine for tuberculosis (bacillus Calmette-Guerin-BCG) or chemotherapeutic agents. Tumors of T2 or higher category are infiltrating tumors and cystectomy is necessary in the majority of cases. Incontinent or continent urinary diversion is presently considered after radical cystectomy. Contra-indications for cystectomy are major co-morbidity and patients not willing to accept the surgery. Bladder preservation with chemo and radiotherapy can be an option in these selected cases.
Keywords: Bladder Neoplasms; Cistektomija; Classification; Cystectomy; Diagnosis; Neoplasm Staging; Novotvorba, stadij; Sečni mehur, novotvorbe; Svetovna, zdravstvena organizacija; Therapy; World Health Organization